Exploring the Potential of Acupressure in Managing Chemotherapy Side Effects: A Case Study on Breast Cancer Patients in Bengkulu, Indonesia - Rahmawati, Diyah Tepi; Metasari, Des; Diniarti, Fiya; Samidah, Ida; Sianipar, Berlian kando (Journal of Current Health Sciences, 2024)
Breast cancer is the most common cancer among women, with significant global mortality rates. The World Health Organization (WHO, 2012) reported that in 2011, over 508,000 women worldwide died from this disease, which accounts for the highest percentage of new cases at 43.3% and a mortality rate of 12.9%. Existing therapies, including surgery, radiotherapy, and chemotherapy, often accompany side effects such as pain, weakness, hair loss, and menstrual disorders. Acupressure, as a form of non-pharmacological therapy, has the potential to mitigate these side effects through the application on meridian points LI4, SP6, and LR3, selected for their relevance to the energy flow affecting pain and the reproductive system. This study investigates the impact of acupressure on points LI4, SP6, and LR3 concerning pain and menstrual disorders in patients with carcinoma mammae undergoing chemotherapy in Bengkulu City. Utilizing a quasi-experimental design and a two-group pretest-posttest with control approach, this study involved 30 participants divided into two groups: 15 in the control group and 15 in the intervention group, selected through purposive sampling. The findings indicated no significant differences in the reduction of pain and menstrual disorders between the groups, with a p-value showing no statistical significance. This suggests that acupressure might be more effective if applied continuously in the early stages of chemotherapy. These findings invite further research to explore the therapeutic potential of acupressure in managing breast cancer, particularly for mitigating chemotherapy side effects.